An Enzyme‐Coated Metal–Organic Framework Shell for Synthetically Adaptive Cell Survival. (5th June 2017) - Liang, Kang; Richardson, Joseph J.; Doonan, Christian J.; Mulet, Xavier; Ju, Yi; Cui, Jiwei; Caruso, Frank; Falcaro, Paolo
Abstract: A bioactive synthetic porous shell was engineered to enable cells to survive in an oligotrophic environment. Eukaryotic cells (yeast) were firstly coated with a β‐galactosidase (β‐gal), before crystallization of a metal–organic framework (MOF) film on the enzyme coating; thereby producing a bioactive porous synthetic shell. The β‐gal was an essential component of the bioactive shell as it generated nutrients (that is, glucose and galactose) required for cell viability in nutrient‐deficient media (lactose‐based). Additionally, the porous MOF coating carried out other vital functions, such as 1) shielding the cells from cytotoxic compounds and radiation, 2) protecting the non‐native enzymes (β‐gal in this instance) from degradation and internalization, and 3) allowing for the diffusion of molecules essential for the survival of the cells. Indeed, this bioactive porous shell enabled the survival of cells in simulated extreme oligotrophic environments for more than 7 days, leading to a decrease in cell viability less than 30 %, versus a 99 % decrease for naked yeast. When returned to optimal growth conditions the bioactive porous exoskeleton could be removed and the cells regained full growth immediately. The construction of bioactive coatings represents a conceptually new and promising approach for the next‐generation of cell‐based research and application, and is an alternative to synthetic biology or genetic modification.